2001
DOI: 10.5194/hess-5-391-2001
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur and nitrogen fluxes and budgets in the Bohemian Forest and Tatra Mountains during the Industrial Revolution (1850-2000)

Abstract: Major fluxes of sulphur and dissolved inorganic nitrogen were estimated in Central European mountain ecosystems of the Bohemian Forest (forest lakes) and Tatra Mountains (alpine lakes) over the industrial period. Sulphur outputs from these ecosystems were comparable to inputs during a period of relatively stable atmospheric deposition (10-35 mmol m -2 yr -1 ) around the 1930s. Atmospheric inputs of sulphur increased by three-to four-fold between the 1950s and 1980s to ~140 and ~60 mmol m -2 yr -1 in the Bohemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 38 publications
2
60
0
Order By: Relevance
“…The deposition sequences used in this study were successfully applied for MAGIC modelling of four lakes in the Tatra Mountains . In general, they have similar shapes to the deposition sequences derived for the region from the EMEP Lagrangian acid deposition model by Schöpp et al (2003), but they are lower and have a broader peak of maximum N deposition in the 1970s and 1990s (consistent with the measured data at the nearby Chopok station; Kopáček et al 2001).…”
Section: Data Sourcessupporting
confidence: 60%
See 1 more Smart Citation
“…The deposition sequences used in this study were successfully applied for MAGIC modelling of four lakes in the Tatra Mountains . In general, they have similar shapes to the deposition sequences derived for the region from the EMEP Lagrangian acid deposition model by Schöpp et al (2003), but they are lower and have a broader peak of maximum N deposition in the 1970s and 1990s (consistent with the measured data at the nearby Chopok station; Kopáček et al 2001).…”
Section: Data Sourcessupporting
confidence: 60%
“…The 1860-2000 trends in bulk deposition of SO 4 2-, NH 4 + , and NO 3 -in the Tatra Mountains come from Kopáček et al (2001) and were based on the following data sources: (i) the measured current deposition at Starolesnianske Lake (southern part; 2000 m a.s.l.) in 1997-2000 unpubl.…”
Section: Data Sourcesmentioning
confidence: 99%
“…A rapid increase in coal burning in the present-day Czech Republic after World War II caused extremely high acid loadings (Kopácek et al, 2001;Hruska et al, 2002), which by the 1980s led to large areas of forest dieback and mortality. High-S emissions in close proximity to mountain ranges with little innate buffering capacity exacerbated the problem.…”
Section: Introductionmentioning
confidence: 99%
“…This area was exposed to heavy atmospheric pollution in the last century (Veselý 1994;Fig. 2), which was followed by significant soil acidification (Kopáček et al 2001(Kopáček et al , 2002a). The MAGIC7 model suggested that soil pH did not vary significantly until the late 1950s, then it began to decrease at the same time with increasing Al concentration.…”
Section: Introductionmentioning
confidence: 99%